Ideal invisibility cloak for heat flow - Tan, Edmund Xin Da (Nanyang Technological University, 2021)
Based on previous studies, many have achieved invisibility cloak in photonics, acoustics, etc. But only a few in literature designed the thermal invisibility cloak. To date, all the thermal invisibility cloaks only work for normal incidence. When designing a novel thermal invisibility cloak, the theory of transformation optics is applied. This research aims to realize the thermal invisibility cloak considering omnidirectional heat flow. In the experiment, we will use a thermal camera to record the heat flow process using MATLAB on the thermal invisibility cloak to show the quality of the design. For simulation, we will be using COMSOL to validate the effectiveness of the thermal invisibility cloak. Results obtained from the thermal invisibility cloak physical experiment and simulation will be used to conclude the findings.